THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE TOWARDS JOB SATISFACTION: STUDY OF LITERATURE - Gian Prayoga; Hadi Sasana (Transpublika Publisher, 2022)
Job satisfaction is a measure of the satisfaction level of workers with their type of work related to their job duties, the work achieved, the form of supervision obtained, as well as a sense of relief and feelings of liking for the work they are doing. This study aims to determine the relationship and role of work environment and organizational culture as factors that affect employee job satisfaction. The method used in this research is literature study using secondary data. The secondary data sources obtained are the results of previous research with related topics and published in accredited national journals in the period 2014 to 2022. The scientific articles analyzed were 30 articles. Based on the analysis of the literature review, the results reveal that work environment and organizational culture each have a positive and significant influence on employee job satisfaction.